Priorities and preferences for care of people with multiple chronic conditions - Mieke Rijken; René Stüssgen; Chantal Leemrijse; Mieke J. L. Bogerd; Joke C. Korevaar (Wiley, 2021)
Abstract Background To guide the development of high‐quality care for people with multiple chronic conditions, partners of the European Joint Action CHRODIS developed the Integrated Multimorbidity Care Model. To assess its suitability for improving care for people with multimorbidity in the Netherlands, the model was piloted in a primary care setting with both patients and care providers. Aim This paper reports on the patient perspective, and aims to explore the priorities, underlying values and preferences for care of people with multimorbidity. Participants and methods Twenty persons with multimorbidity (selected from general practice registries) participated in a focus group or telephone interview. Subsequently, a questionnaire was completed by 863 persons with multimorbidity registered with 14 general practices. Qualitative data were thematically analysed and quantitative data by means of descriptive statistics. Results Frequently prioritized elements of care were the use of shared electronic health records, regular comprehensive assessments, self‐management support and shared decision making, and care coordination. Preferences for how these elements should be specifically addressed differed according to individual values (eg weighing safety against privacy) and needs (eg ways of coping with multimorbidity). Conclusion The JA‐CHRODIS Integrated Multimorbidity Care Model reflects the priorities and preferences for care of people with multimorbidity in the Netherlands, which supports its relevance to guide the development of person‐centred integrated care for people with multiple chronic conditions in the Netherlands. Patient contribution European patient experts contributed to the development and applicability assessment of the JA‐CHRODIS Integrated Multimorbidity Care Model; Dutch patients participated in focus groups, interviews and a survey.